Effect of Structure on Vertical and Horizontal Wicking Performance Concerning Jute (Chorchorus Olitorius) and Water. Issue 14 (28th October 2022) - Sengupta, Surajit; Bhowmick, Manik; Karmokar, Sujoy
ABSTRACT: Vertical and horizontal wickings were studied for jute, a lingo-cellulosic natural fiber, as fiber, yarn, woven fabric, and nonwoven. The effect of yarn parameters (linear density, twist density, and tension), fabric type (plain woven, twill woven, and nonwoven) and nonwoven parameters (parallel laid, cross laid, areal density, punch density, and depth of needle penetration) were observed and analyzed using a fabricated setup for wicking testing. Wetting of jute with water was studied by measuring contact angle using Sissili-drop method. The rate of wicking shows two distinct parts: instantaneous and time dependant. The horizontal wicking is always higher than the vertical wicking. The weft shows better wicking than warp yarn followed by two-ply yarn. Yarn twist level and linear density play a significant role. Twill fabric shows better wicking than plain-woven fabric. Wicking effect of needle-punched nonwoven shows lower than woven fabric. It is negatively correlated with areal density and positively correlated with punch density. It will help to design a textile from jute, where wicking plays a significant role.